Cold War Captives : Imprisonment, Escape, and Brainwashing - Carruthers, Susan L. (Susan Lisa) (Book collections on Project MUSE., 2009)
Susan Carruthers offers a provocative history of early Cold War America, in which she recreates a time when World War III seemed imminent. She shows how central to American opinion at the time was a fascination with captivity & escape. Captivity became a way to understand everything.